1989
DOI: 10.1104/pp.91.4.1251
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ethylene in the Geotropic Response of Bermudagrass (Cynodon dactylon L. Pers.) Stolons

Abstract: We studied the relationship between ethylene and gravityinduced upward bending of bermudagrass (Cynodon dactylon L. Pers.) stolons. Ethylene production begins within 3 hours of the onset of gravistimulation, and increases thereafter until the 15th hour, after which it declines. There is a close positive relationship between ethylene production and upward bending during the first 12 hours of gravistimulation. Incubation of stolons with AgNO3 did not prevent ethylene evolution but delayed upward bending. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…The ratio of red/far red light, can also finely regulate the differentiation of stolons and shoots through phytochrome-mediated photoassimilate partitioning [15, 16]. Phytohormones, including auxin, ethylene and gibberellin, synergistically adjust the morphology of bermudagrass by regulating the development and growth of stolons and shoots [13, 17]. These observations collectively imply that the plant architecture characteristics of bermudagrass could be modified by external factors.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of red/far red light, can also finely regulate the differentiation of stolons and shoots through phytochrome-mediated photoassimilate partitioning [15, 16]. Phytohormones, including auxin, ethylene and gibberellin, synergistically adjust the morphology of bermudagrass by regulating the development and growth of stolons and shoots [13, 17]. These observations collectively imply that the plant architecture characteristics of bermudagrass could be modified by external factors.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene is also known to play an important role in the gravitropic response, in spite of the fact that there are opposing reports based on the relationship between the gravitropic response and ethylene production (Kaufman et al 1985, Harrison and Pickard 1986, Balatti and Willemoes 1989, Woltering 1991). It has been reported that ethylene is responsible for decreased starch levels in the columella cells, and thus, possibly results in inhibition of the gravitropic response of Arabidopsis roots (Guisinger and Kiss 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of ethylene in gravitropism is still controversial, since inhibitors of ethylene synthesis or action were not always effective in inhibiting the gravitropic response of various systems (Wheeler and Salisbury, 1981;Clifford et al, 1983;Kaufman et al, 1985;Balatti and Willemoes, 1989;Woltering, 1991). Also, the role of the increased ethylene production obtained in various plant organs upon their reorientation from the vertical to the horizontal is still obscure (Wheeler et al, 1986;Harrison and Pickard, 1989;Woltering, 1991).…”
mentioning
confidence: 99%